Recent enhancement of central Pacific El Niño variability relative to last eight centuries - Yu Liu (Nature Portfolio, 2017)
El Niño events in the Central Pacific may be changing due to climate change, but long records to support this are lacking. Here, the authors present sea surface temperature reconstructions from tree cellulose for the last 800 years which suggest the variability of Central Pacific El Niño events has increased.